The demographics of energy and mobility poverty: Assessing equity and justice in Ireland, Mexico, and the United Arab Emirates - Furszyfer del Rio, Jonathan (2023)
Energy and mobility poverty limits people’s choices and opportunities and negatively impinges upon structural economic and social welfare patterns. It also hampers the ability of planners to implement more equitable and just decarbonization pathways. Research has revealed that climate policies have imposed a financial burden on low-income and other vulnerable groups by increasing food and energy prices, leading as well to global inequality. Similarly, researchers have warned that in developing countries, emission mitigation policies could increase poverty rates and even frustrate progress towards universal access to clean energy. This research explores whether low-income social groups experience a 'double energy vulnerability', a situation that simultaneously positions people at heightened risk of transport and energy poverty. We investigate this 'double vulnerability' through original data collection via three nationally representative surveys of Mexico (N = 1,205), the United Arab Emirates (N = 1,141), Ireland and Northern Ireland (N = 1,860). We draw from this original data to elaborate on the sociodemographic attributes, expenditure and behaviour emerging from energy and transport use, focusing on themes such as equity, behaviour and vulnerability. We propose energy and transport poverty indexes that allow us to summarize the key contributing factors to energy and transport poverty in the countries studied and uncover a strong correlation between these two salient forms of poverty. Our results suggest that energy and transport poverty are common issues regardless of the very different national, and even sub-national, contexts. We conclude that energy and transport poverty requires target policy interventions suitable for all segments of society, thus enabling contextually-tailored, just energy transitions.